Implementasi QS. Al-Baqarah Ayat 30 dan QS. Adz-Dzariyat Ayat 56 dalam Pendidikan Santri di Pondok Pesantren Qur’an dan IT Al-Mahir - Muzhaffar, Zidan Arif; Mujiburrohman, Mujiburrohman (Lembaga Yasin AlSys, 2026)
This study aimed to analyze the implementation of QS. Al-Baqarah verse 30 and QS. Adz-Dzariyat verse 56 in the education of santri at Pondok Pesantren Qur’an dan IT Al-Mahir, positioning the human role as khalifah on earth and the purpose of creation as worship of Allah as the primary normative framework. The research employed a qualitative method with a case study approach, using participant observation, in-depth interviews, and document analysis related to the curriculum, daily activities, and student development programs. The findings show that the values contained in these two verses are implemented through an emphasis on akhlaq formation, the strengthening of worship, and the holistic development of santri in spiritual, intellectual, and skills-based dimensions, including the responsible use of information technology. Implementation is carried out in a structured manner through the integration of khalifah and ubudiyyah values into the curriculum, the habituation of worship and adab in daily activities, and spiritual guidance that underscores students’ personal accountability before Allah and their social roles in the wider community. These results contribute to the development of Islamic education grounded in Qur’ani values and have implications for strengthening the quality of education at Pondok Pesantren Qur’an dan IT Al-Mahir as an institution that prepares santri to be persons of character and knowledge, committed to devotion to Allah and service to society.